Skrining Fitokimia dan Aktivitas Antioksidan pada Kijing (Pylsbryoconcha Sp) dengan Pelarut Berbeda - Yasti Sari; Syahrul Syahrul; Dian Iriani (Jurnal Teknologi dan Industri Pertanian Indonesia, 2021)
Kijing (Pilsbryoconcha sp) is a type of freshwater mussel that has 2 shells (Bivalvia), and its existence as a good source of animal protein at a relatively cheap price. The water of the Paku River is one of the kijing producers located in the Kampar Kiri sub-district Kampar Riau Province. The types of solvents used in the extraction process consist of n-hexane (non-polar), ethyl acetate (semi-polar) and methanol (polar). The purpose of this study was to determine the most suitable type of solvent to extract bioactive compounds. The parameters were yield, identification of active compounds and antioxidant activity. The results showed the highest yield of kijing was found using methanol (1.29%). The active compounds of kijing were alkaloids, steroids, flavonoids and phenolic. The methanol extract had a moderate antioxidant activity with an IC value of 215,62 ppm.